EFFECT OF USING THE LIGHT REFRACTION EXPERIMENT DEVICE FOR STUDENT'S LEARNING OUTCOMES IN JUNIOR HIGH SCHOOL - Siti Arianti Oktaria; Noer Iskandar; Muhammad Syafii; Yennita Yennita (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
This research aims to describe the effect of cognitive learning outcomes of students with the use of light refraction experimental devices and test whether there is an effective influence on the science learning outcomes of science physics. The type of research is a pre-experimental research with a one shot case study design. The subjects in this research were class VIII Hang Nadim SMP1 Pekanbaru which amounted to 39 students. The data collection instrument used was a written test of students' cognitive learning outcomes in the form of a post-test with data collection techniques in the form of giving tests. The data analysis technique used is descriptive analysis technique, to provide an overview of the effect of the use of light refraction experimental devices on students 'cognitive learning outcomes by looking at students' absorption and learning effectiveness. The results of data analysis obtained were 34 students in the category of excellent absorption in the percentage of 87.17%, 2 students in the category of good absorption with a percentage of 5.12% and 3 students in the absorption category quite well with a percentage of 7.16 %. Overall, the average absorption of students was 92.48% and was in the very good and very effective category. Based on data analysis it can be concluded that the use of light refraction experiment devices has a very good effect on students' cognitive learning outcomes in light material in class VIII Hang Nadim SMP1 Pekanbaru.